Factors Associated with Occupational Stress among University Teachers in Pakistan and Finland - Naima Akhtar Akhtar Malik; Kaj Björkqvist; Karin Österman (Universitas Ahmad Dahlan, 2017)
Abstract The study examines the interplay of psychosocial factors and works conditions on occupational stress among 531 university teachers in Pakistan and Finland with the help of a web-based questionnaire. Results from an MANOVA revealed that good working conditions, social support at work, and promotion and development opportunities were rated as significantly better by the Finnish sample. Workplace bullying occurred considerably less often in Finland than in Pakistan. Male Pakistani teachers reported significantly higher levels of workplace bullying than any other group. Although the working conditions, social support, and promotion and development opportunities were better, and less bullying appeared in Finland than in Pakistan, but the difference in stress symptoms between the two countries was not significant. Keywords: Occupational stress, social support, university teachers, workplace bullying, work conditions, Pakistan, Finland.